The Educational Qualifications and Job Satisfaction of MSU-IIT Academic Administrators and the Organizational Effectiveness Profile of the Institute: Basis for an Administrative Development Program - T. Roxas, Alita (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
he study seeks to determine the relationship between the perceived organizational effectiveness profile of MSU-IIT with two other variables, namely, the perceived adequacy of the qualifications of its academic administrators and the selection criteria used, and the level of job satisfaction of the academic administrators. The qualifications of faculty administrators which are brought into scrutiny are educational attainment, length of service in MSU-IIT, status of ap-pointment, and return service after a study grant. The level of job satisfaction of the administrators is determined by making use of Herzberg's hygience and motivation factors. Organizational effectiveness pertains to the perceived capability of the MSU-IIT to meet the standards of innovation-adaptation, direc-tion-goal clarity, productivity-accomplishment, participation-openness, stability-control, external support-resource acquisition, commitment-morale, and documentation-information management. The stay reveals that the respondents perceive the minimum qualifications and the evaluation criteria for the selection of academic administrators to be adequate. It also shows that academic administrators are satisfied with their administrative jobs. Organizational effectiveness as measured by the eight pairs of criteria are often found to occur. With the application of the Pearson r product moment correlation technique the stuay is able to establish a significant relationship between the per-cerved adequacy of the munmum qualifications and evaluation criteria for the selection of academic administrators and the perceived organizational effectiveness profile of MSU-III. A significant relationship is established, likewise, between the motivator variables and the organizational effectiveness variables.